Institutional choice and global commerce - Jupille, Joseph Henri; Mattli, Walter; Snidal, Duncan; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
Why do institutions emerge, operate, evolve and persist? Institutional Choice and Global Commerce elaborates a theory of boundedly rational institutional choice that explains when states USE available institutions, SELECT among alternative forums, CHANGE existing rules, or CREATE new arrangements (USCC). The authors reveal the striking staying power of the institutional status quo and test their innovative theory against evidence on institutional choice in global commerce from the nineteenth through the twenty-first centuries. Cases range from the establishment in 1876 of the first truly international system of commercial dispute resolution, the Mixed Courts of Egypt, to the founding and operation of the General Agreement on Tariffs and Trade, the World Trade Organization, and the International Accounting Standards Board. Analysts of institutional choice henceforth must take seriously not only the distinct demands of specific cooperation dilemmas, but also the wide array of available institutional choices.
Introduction : institutional choice in global commerce -- International institutional choice : cooperation, alternatives and strategies -- Building Theseus' ship : why the ITO failed, the GATT succeeded and the WTO emerged -- Creating the first International Court of Commercial Dispute Resolution : the mixed courts of Egypt -- Commercial complexity and institutional choice in the GATT era -- Institutional choice in global accounting governance -- Conclusion : overview and institutional theories compared.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: International agencies; International trade; Electronic books